Um museu virtual em memória do escritor Pedro Wayne - Leite, Vera Lucia Scotto (2019)
This dissertation addresses the preservation and access of the cultural heritage of writer Pedro Wayne and how this heritage can be presented to the public, thus strengthening the identity of the writer in the cultural scene, since the work of the writer This dissertation addresses the preservation and access of the cultural heritage of writer Pedro Wayne and how this heritage can be presented to the public, thus strengthening the identity of the writer in the cultural scene, since the work of the writer has relevance in the literature of Rio Grande do Sul. The samples used for the application of this work were manuscripts, photographs and personal objects of the writer. Original photographs and manuscripts are documents, sources of evidence, which carry the writer's story, and the information that is contained in the objects serves as memory supports about the individual's life trajectory with emphasis on the community, where he was inserted. Thus, the work is justified by the importance of the collection, aiming at the permanence of the information contained therein. The objective of this work was to rescue the memory of writer Pedro Wayne through his collection, in addition to inventorying, preserving and disseminating the existing collection in the Pedro Wayne Memorial Collection, located at the Pedro Wayne Culture House in Bagé/RS. The research is considered applied, with exploratory qualitative approach, in relation to its bibliographic classification, also having characteristics of a case study. Data collection was achieved through literature review and description of the samples that form a whole. The result was the implementation of a tool that will serve as a rescue of the memory of Pedro Wayne's writer, aiming at the preservation and access to his personal collection.